Protective effect of vitamin E on oxidative stress and sperm apoptosis in diabetic Mice - Khadijeh Mirzaei Khorramabadi; Ali Reza Talebi; Abolghasem Abbasi Sarcheshmeh; Aghdas Mirjalili (Shahid Sadoughi University of Medical Sciences, 2019)
Background Generation of free radicals and oxidative stress are a major contributor to diabetes. These factors lead to the development of diabetic testicles disorders. Objective In this study, the protective effect of vitamin E on functional disorders associated with diabetes induced oxidative stress in male reproductive systems has been investigated. Materials and Methods Thirty-three adult male Mice were divided into control, diabetic, and untreated diabetic groups. Streptozotocin was used to induce diabetes. In the treated group, vitamin E was given to the Mice intraperitoneally for 30 days. Then, animals were anesthetized and sacrificed. Animal testicles were isolated and homogenized in phosphate buffer and used for measuring sperm count, motility and survival of sperm, MDA concentration and antioxidant capacity (TAC). Apoptosis was also performed with the TUNEL test. Results The results of reduction (12.03 ± 98.11) TAC, MDA concentration (-28.5 ± 2.58), sperm motility (unstable sperma= 86.4 ± 7.48), sperm count (171.51), Sperm morphology (natural morphology= 49.69 ± 31.93) and abnormal morphology (9.77 ± 49.7) with increased oxidative damage. These changes were statistically significant in comparison with the control group for all variables other than MDA (p= 0.05). Treatment of vitamin E diabetic Mice improved the ability of antioxidants to prevent oxidative damage in the testicles, restore the sperm movement, and increase the number of normal sperm as well as TAC. The level of apoptosis in the treated group has decreased compared to the untreated group. Conclusion Vitamin E protects the reproductive system against diabetes mellitus. Therefore, it was concluded that vitamin E may be a suitable agent for protecting the sperm and testicular parameters against undesirable effects of diabetes.